Character education in schools implementing national curriculum and international baccalaureate - Hotmaulina Sihotang; Stevanie Datrix (Teraputik: Jurnal Bimbingan dan Konseling)
The purpose of the study was to evaluate the implementation of the character education program of Junior and Senior High School Victory Plus School using the national curriculum and International Baccalaureate. The research method used is mix method. The result of data analysis showed that the average self-concept score was 2.65 (less good); selfmanagement is 2.73 (good); and social services is 2.73 (good) in the implementation of courageous, honest, active, mindful, innovative, open minded, and nobel (champion) value. The value of champion is relevant to the value of the national curriculum character but the value of hard work, religion, democracy, the spirit of nationality, and the love of the homeland have not yet appeared. The balanced and reflective values in the learner profile are not yet visible.